IMPROVING MECHANISMS FOR THE DEVELOPMENT OF STUDENTS’ INDEPENDENT LEARNING COMPETENCIES IN THE CREDIT-MODULE SYSTEM - Sattarova Gulnoza Salim kizi (International Journal of Literature and Language Studies, 2026)
The systematic transition of global higher education institutions toward the European Credit Transfer and Accumulation System (ECTS) represents a fundamental epistemological shift from teacher-centered pedagogies to student-centered academic autonomy. This comprehensive research report investigates the structural, pedagogical, and technological mechanisms required to develop students’ independent learning competencies within the credit-module system (CMS). The study is deeply contextualized within the ongoing educational reforms in the Republic of Uzbekistan, driven by national strategic directives such as the “Concept for the Development of the Higher Education System until 2030” and Cabinet of Ministers Resolution No. 824. Under the CMS, independent study constitutes the primary vector of academic labor, accounting for 50% to 70% of a student’s total workload. However, empirical observations indicate that students transitioning from traditional, highly structured educational environments frequently lack the requisite metacognitive, analytical, and digital competencies to navigate this autonomy effectively. Utilizing an advanced mixed-methods research design that encompasses extensive policy document analysis, empirical survey data from diverse university cohorts, and computational data modeling via Python, this report systematically deconstructs the operational realities of the CMS. The findings confirm that independent learning cannot be treated as a passive accumulation of unstructured study hours; it requires deliberate pedagogical engineering. The analysis identifies critical mechanisms for success, including the deployment of comprehensive syllabi acting as learning contracts, the integration of flipped classrooms and project-based learning (PBL), and the utilization of sophisticated Learning Management Systems (LMS) such as Moodle and HEMIS. Furthermore, the report critically addresses systemic barriers, including faculty adaptation resistance, the scarcity of native-language academic resources, and the vulnerability of continuous assessment models to academic dishonesty and “scholarship pressure.” Ultimately, the report proposes a multidimensional, data-driven framework designed to optimize independent learning trajectories, ensuring that graduates possess the self-regulated learning capabilities necessary to maintain professional competitiveness in the rapidly evolving global knowledge economy.